Burning by numbers: A pilot study using quantitative petrography in the analysis of heat‐induced alteration in burned bone - Carroll, Emily L.; Squires, Kirsty E. (International journal of osteoarchaeology, 2020)
In the past, experimental research into the histomorphological examination of burned human bone has led to the creation of a criterion for assessing burning intensity, which can be used to infer firing conditions in both archaeological and forensic contexts. Current methods visually compare the microscopic alterations in burned bone with modern bone samples fired at known temperatures and durations. Despite the benefits of this approach, it is hindered by the use of qualitative analysis, which is subject to the expertise of the examiner. This paper reviews previous histomorphological studies of burned bone and presents a new protocol for producing burned bone thin sections. It also introduces quantitative petrography as an alternative statistical method for categorising burning intensity. Four categories of burning intensity were calculated based on the quantified heat‐induced changes identified in a pilot study examining burned porcine bone. These categories were consistent with those produced using more traditional qualitative methods, demonstrating that the results produced in this pilot study are reliable. An interobserver study showed the repeatability of this new method by both anthropologists and non‐anthropologists.